2011
DOI: 10.1080/03081060.2011.554706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different contraflow strategies for hurricane evacuation in Charleston, South Carolina

Abstract: Limited specific evidence is available on the effectiveness of using contraflow as an evacuation traffic management tool. This study was conducted to determine the best combination of strategy options for evacuating Charleston, SC, along route I-26 during the event of a hurricane or other events. PARAMICS microscopic traffic simulator was used to evaluate the impact of each combination of evacuee response timing and traffic control strategy, such as contraflow, with respect to average vehicular travel time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Driver behavior modeling is controlled by various parameters with the capability of modeling different segments or types of roadways with multiple driver behaviors. The [26]. The researchers obtained and overlaid plans for construction projects that would be complete by the base year of 2014 because aerial images were not yet available.…”
Section: Model Buildingmentioning
confidence: 99%
“…Driver behavior modeling is controlled by various parameters with the capability of modeling different segments or types of roadways with multiple driver behaviors. The [26]. The researchers obtained and overlaid plans for construction projects that would be complete by the base year of 2014 because aerial images were not yet available.…”
Section: Model Buildingmentioning
confidence: 99%
“…Past work on spatiotemporal evacuation trigger buffers (Dennison et al 2007, Larsen et al 2011 and the use of volunteered geographic information (Pultar et al 2010) have been shown to effectively model the safe evacuation of people from wildfires. Research in transportation networks and how they can be optimized to evacuated citizens from hurricanes has also proven successful at simulating the movement of people away from the hurricane's impacts (Naghawi and Wolshon 2010, Wang et al 2010, Fries et al 2011. The model in this paper extends this work by including the evacuations of building contents rather than the evacuations of people.…”
Section: Discussionmentioning
confidence: 95%
“…Evacuations help to protect the lives of citizens who are at risk during a disaster. An extensive literature has investigated the spatiotemporal simulation of evacuating people from fires (Cova et al 2005, Dennison et al 2007, Larsen et al 2011, Shenhar et al 2012, hurricanes (Chen et al 2006, Chiu et al 2008, Naghawi and Wolshon 2010, Wang et al 2010, Fries et al 2011, and floods Ahmad 2005, Kim et al 2011). Two spatial decision support systems (SDSS) exist that aid in estimating evacuations during disasters such as hurricanes, floods and earthquakes (HURREVAC, http://www.hurrevac.com/ and Hazus-MH, http://www.fema.gov/hazus).…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation